Longitudinal Ocular Surface Microstructural Findings After Switching to Preservative-Free Dorzolamide/Timolol in POAG: An Exploratory IVCM Pilot Case Series - Ana Sanseau; Arturo Burchakchi; Fernando Cataldi; Héctor Fontana; Alejo Peyret; Giselle Rodríguez; Ailín Fantacone; María Silvia Passerini; Javier Fernando Casiraghi; Analía Luna (International Journal of Translational Medicine, 2026)
Background and Objectives: To describe longitudinal ocular-surface microstructural findings on in vivo confocal microscopy (IVCM) after switching from benzalkonium chloride-preserved dorzolamide 2%/timolol 0.5% (BAK-DT) to preservative-free dorzolamide 2%/timolol 0.5% (PF-DT) in four patients with primary open-angle glaucoma (POAG) and ocular surface disease (OSD). Materials and Methods: This prospectively planned, exploratory pilot case series included four participants (eight eyes) from a previously published 30-participant parent study. IVCM was performed at baseline and months 3, 6, 9, and 12. Because only four independent participants contributed both eyes, analyses were descriptive, and no inferential tests were performed. Results: All four participants completed follow-up. From baseline to month 12, median superficial corneal epithelial cell density increased by 2010.00 cells/mm2 and median conjunctival epithelial cell density by 3261.5 cells/mm2; median stromal reflectivity decreased by 0.07 arbitrary units and median dendritic cell density by 75.49 cells/mm2. Both eyes of each participant changed in the same direction for these four outcomes. Other IVCM measures showed no uniform temporal pattern. Conclusions: The temporal IVCM changes observed after the therapeutic switch were compatible with lower ocular-surface inflammatory activity. These preliminary findings should be interpreted cautiously and confirmed in larger controlled studies.